A study on planning for interconnected renewable energy facilities in Hokkaido, Japan. (15th May 2015) - Obara, Shin'ya; Utsugi, Yuta; Ito, Yuzi; Morel, Jorge; Okada, Masaki
Highlights: Stabilizing power distribution by linking renewable energy facilities was investigated. Algorithm for interconnection of renewable energy over a large area was developed. Optimum layout and capacity of distributed renewable energy were clarified. Power linking and supplementing renewable energy over a large area were examined. Abstract: In this paper, to optimize the kind and capacity of renewable energy installed in each area, an optimization program was developed using a simple genetic algorithm (GA). In the proposed algorithm, the kind and capacity of renewable energy was expressed using a chromosome model. The most efficient and economical system could be identified by applying the model in a random computer search. A case study was developed to test the proposed algorithm. In the case study, a solar power station was installed near 14 cities in Hokkaido, Japan, and a wind power station was installed seven areas. Using the algorithm, the system planning requirements for the interconnection of these renewable energy facilities over a large area were optimized. On the basis of these results, the kind and capacity of renewable energy considered to be the most economically advantageous to the region were identified and evaluated. Using the proposed optimization algorithm for planning and design, an efficient, economical, and interconnected system of electrical power could be realized from renewable energy over a large area.